RF transistor amplifier design and analysis - Ng, Chin Yong (Nanyang Technological University, 2022)
A negative impedance converter (NIC) is an active 2 port network that generates non-foster elements such as negative capacitor or inductor. It can be realised using transistors or operational amplifier (op-amp). In this report, 2 different topologies of op-amp based NIC were discussed and, in the process, a formula that governs the input impedance of these topologies was developed based on observations. This formula can be used to analyse and account for the differences between these topologies. First, the derivation of the formula using ideal op-amp with finite gain will be presented, followed by the verification of this formula. Next, an attempt to extend this formula to nonideal op-amp is made. Although the nonideal op-amp formula has yet to be developed, the strong connection with the parameters found in the ideal op-amp formula may serve as a steppingstone towards developing the nonideal op-amp formula. This would help in designing the desired non-foster element for real life application.